2014
DOI: 10.1186/1477-7819-12-246
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma: clinicopathological profile and challenges of management in a resource-limited setting

Abstract: BackgroundHepatocellular carcinoma is one of the most common cancers worldwide and its incidence is reported to be increasing in resource-limited countries. There is a paucity of published data regarding hepatocellular carcinoma in Tanzania, and the study area in particular. This study describes the clinicopathological profile of hepatocellular carcinoma in our local setting and highlights the challenging problems in the management of this disease.MethodsThis was a retrospective study of histopathologically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…In this study, in HCC patients aged 41‐60 years old, there were 480 (83.92%) males and 92 (16.08%) females, and in HCC patients ≥61 years old, there were 435 (72.62%) males and 164 (27.38%) females. This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, as well as other local and regional studies …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, in HCC patients aged 41‐60 years old, there were 480 (83.92%) males and 92 (16.08%) females, and in HCC patients ≥61 years old, there were 435 (72.62%) males and 164 (27.38%) females. This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, as well as other local and regional studies …”
Section: Discussionsupporting
confidence: 94%
“…This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, 16,17 as well as other local and regional studies. 18,19 In addition, the finding that females were significantly older than males might also refect a course in disease progression. Previous studies have shown that the liver fibrosis status of women changes with age, which may be due to changes in the reproductive status, 20 Therefore, less treatment measures will affect the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common and serious malignancies worldwide (1,2). Due to its highly aggressiveness and poor prognosis, patients with advanced HCC are not candidates for local/regional surgical resection (3)(4)(5). Cirrhosis of any etiology is a risk factor for HCC, which include infection with hepatitis B virus (HBV) or hepatitis C virus (HCV), alcoholic cirrhosis and exposure to environmental toxins such as aflatoxin (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer is accounted as 8 % (n = 608,700) of all cancer deaths worldwide [1], and the third leading cause of cancer-related deaths in the USA [2]. Hepatocellular carcinoma is the third leading cause of cancer deaths worldwide [3] with the prevalence 16-32 times higher in developing countries than in developed countries [4].…”
Section: Introductionmentioning
confidence: 99%